Getting Energy Prices Right : From Principle to Practice - Parry, Ian (International Monetary Fund, 2014)
Energy taxes can produce substantial environmental and revenue benefits and are an important component of countries' fiscal systems. Although the principle that these taxes should reflect global warming, air pollution, road congestion, and other adverse environmental impacts of energy use is well established, there has been little previous work providing guidance on how countries can put this principle into practice. This book develops a practical methodology, and associated tools, to show how the major environmental damages from energy can be quantified for different countries and used to design the efficient set of energy taxes.